Fibrinogen and the prediction of residual obstruction manifested after pulmonary embolism treatment. Issue 5 (15th November 2018) - Planquette, Benjamin; Sanchez, Olivier; Marsh, James J.; Chiles, Peter G.; Emmerich, Joseph; Le Gal, Grégoire; Meyer, Guy; Wolfson, Tanya; Gamst, Anthony C.; Moore, Roger E.; Gugiu, Gabriel B.; Morris, Timothy A.
Residual pulmonary vascular obstruction (RPVO) and chronic thromboembolic pulmonary hypertension (CTEPH) are both long-term complications of acute pulmonary embolism, but it is unknown whether RPVO can be predicted by variants of fibrinogen associated with CTEPH. We used the Akaike information criterion to select the best predictive models for RPVO in two prospectively followed cohorts of acute pulmonary embolism patients, using as candidate variables the extent of the initial obstruction, clinical characteristics and fibrinogen-related data. We measured the selected models' goodness of fit by analysis of deviance and compared models using the Chi-squared test. RPVO occurred in 29 (28.4%) out of 102 subjects in the first cohort and 46 (25.3%) out of 182 subjects in the second. The best-fit predictive model derived in the first cohort (p=0.0002) and validated in the second cohort (p=0.0005) implicated fibrinogen Bβ-chain monosialylation in the development of RPVO. When the derivation procedure excluded clinical characteristics, fibrinogen Bβ-chain monosialylation remained a predictor of RPVO in the best-fit predictive model (p=0.00003). Excluding fibrinogen characteristics worsened the predictive model (p=0.03). Fibrinogen Bβ-chain monosialylation, a common structural attribute of fibrin, helped predict RPVO after acute pulmonary embolism. Fibrin structure may contribute to the risk of developing RPVO. Fibrinogen helps predict residual pulmonary vascular obstruction after pulmonary embolism: results from the PROMPT study http://ow.ly/G7pY30m2HU6